Vertical Integration: Scale Distortions, Partial Integration, and the Direction of Price Change - Quirmbach, Herman C. (Quarterly Journal of Economics, 1986)
Two new features are introduced in a standard model of forward vertical integration by an intermediate good monopolist into a contestable downstream industry. First, U-shaped average costs replace constant returns in the downstream industry. Second, the effect of subjecting the monopolist to the pressure of upstream entry is explored. It is found that monopoly pricing of the intermediate good can distort the scale as well as the input proportions of the downstream firms. Either distortion leads to integration, but here integration may be partial rather than full. Prices rise with partial integration when there is no upstream entry, but prices fall when upstream entry is free.